Motif Melakukan Electronic Word of Mouth oleh Konsumen - Rosmalia Ahmad; Diah Febrina (CoverAge: Journal of Strategic Communication, 2018)
Electronic word of mouth communication (eWOM) can reach more consumers through new media such as social media, blog, website, and so forth. The purpose of this study is to determine the level of motivation to perform electronic word of mouth (eWOM) by consumers. This research used electronic word of mouth (eWOM) and the motives for giving electronic word of mouth (eWOM) as a concept. The results show that altruism, social benefits, and venting feeling are considered as the motivation for giving electronic word of mouth (eWOM) by consumers. While self-improvement is a dimension that does not motivate consumers to do electronic word of mouth (eWOM).